Research of Health Management on Satellite Communication Earth Station Platform Based on Engineering-Oriented Method - Qing XUE; Yusheng LIN; Yang KOU; Yongchi ZHANG; Jing ZHANG; Shaofei Wang (天地一体化信息网络)
Based on the practical experience in satellite communication network fi eld, considering the existing problems in current system, regarding the typical earth station platform as research object, this paper did research of health management on satellite communication earth station platform based on engineering-oriented method.The analysis for health management mode was conducted associated with practical work mode and fl ow path, then, a typical indicator data classifi cation way was proposed based on inservice equipments and system, and we showed some examples.Finally, the fault diagnosis and prognostic method, the health assessment method, and the prognostic method for remaining life were proposed considering the real situation of our satellite communication system, which was an advanced thought for engineering-oriented health management method on satellite communication network fi eld.